Clinical and immune-related factors associated with exacerbation in adults with well-controlled generalized myasthenia gravis - Bi, Zhuajin; Zhan, Jiayang; Zhang, Qing; Gao, Huajie; Yang, Mengge; Ge, Huizhen; Gui, Mengcui; Lin, Jing; Bu, Bitao (Frontiers in Immunology, 2023)
Objectives: To describe the clinical predictors and immune-related factors for exacerbation in adults with well-controlled generalized myasthenia gravis (GMG). Methods: We conducted a retrospective analysis of 585 adults with well-controlled GMG from our institutionclinic to explore the risk factors for exacerbation. Furthermore, propensity score matching was used to compare the proportions of lymphocyte subsets, the levels of immunoglobulin, complement and anti-acetylcholine receptor antibody (AChR-ab) in peripheral blood of 111 patients with exacerbations and 72 patients without exacerbations. Results: 404 patients (69.1%) experienced at least one exacerbation and the median (interquartile range) time to the first exacerbation was 1.5 years (0.8-3.1 years). Multivariable Cox regression analysis showed that age at onset, disease duration before enrollment, more severe MGFA classification (class III and IV-V), AChR-ab, MuSK-ab, thymus hyperplasia, early prednisone in combination with immunosuppressants treatment, and thymectomy were independent predictors for the exacerbations (hazard ratio [HR] = 1.011, 1.031, 1.580, 1.429, 2.007, 2.033, 1.461, 0.798 and 0.651, respectively). Propensity-matched analysis compared 51 patient pairs. After propensity score matching, the peripheral blood proportions of CD3-CD19+ B cells, ratio of CD3+CD4+/CD3+CD8+ T cells, and AChR-ab levels were significantly increased, and the peripheral blood proportions of CD3+CD8+ T and CD4+CD25+CD127low+ regulatory T cells (Tregs) were significantly decreased in patients with exacerbation compared with those without exacerbation (all P < 0.05). Conclusion: The MG exacerbations were more frequent in those patients with older onset age, longer disease duration, more severe MGFA classification, positive AChR-ab, and lack of combined immunotherapy or thymectomy treatment. On the other hand, the peripheral blood CD3-CD19+ B cells, CD3+CD8+ T cells, Tregs, and AChR-ab may be involved in the course of GMG exacerbation.